Immune algorithm for solving the smooth economic dispatch problem - Aragón, Victoria S. (2015)
In this paper, an algorithm inspired on the T- Cell model of the immune system is presented, it is used to solve Economic Dispatch Problems with smooth objective function. The proposed approach is called IA EDP S, which stands for Immune Algorithm for Economic Dispatch Prob- lem for smooth objective function, and it uses as differentiation process a redistribution power op- erator. The proposed approach is validated using five problems taken from the specialized litera- ture. Our results are compared with respect to those obtained by several other approaches.